Treatment of Seborrheic Keratosis by High Frequency Focused Ultrasound – An Early Experience with 11 Consecutive Cases - Calik J; Migdal M; Zawada T; Bove T (Dove Medical Press, 2022)
Jacek Calik,1 Monika Migdal,1 Tomasz Zawada,2 Torsten Bove2 1Old Town Clinic, Wrocław, Poland; 2TOOsonix A/S, Hoersholm, DenmarkCorrespondence: Torsten BoveTOOsonix A/S, Agern Alle 1, Hoersholm, DK-2970, Denmark, Tel +45- 2059 2999, Email torsten.bove@toosonix.comPurpose: High intensity focused ultrasound operating at 20 MHz has been demonstrated as a safe and efficient treatment modality for a range of dermatological indications. The method is potentially also applicable to removal of seborrheic keratosis.Patients and Methods: A total of 54 seborrheic keratoses in 11 volunteer subjects (8 women and 3 men, average age 51.5 ± 13.2 years) were treated in a single session with a medical 20 MHz high intensity focused ultrasound device developed for dermatological conditions. Handpieces with nominal focal depths of 0.8 mm below the skin surface were used to administer acoustic energy of 0.99- 1.2 J/dose. An integrated dermoscope in the handpiece was used to monitor the treatment in real-time. Treatment efficacy and side-effects were assessed directly after treatment and at follow-up 4- 15 weeks after treatment.Results: The treatment showed positive results in 96.3% of the cases. About 68.5% of the cases were classified as complete response and 27.8% of the cases as partial response. Two cases (3.7%) did not respond to treatment and were classified as stable condition. No subjects experienced worsening of their condition, and no treatment received the classification of progressive condition. Side effects were primarily redness in the treatment area due to superficial telangiectasia, mild scarring, and persisting and slow-healing lichen planus-like keratosis. No adverse events were observed.Conclusion: HIFU is concluded to be a safe and efficient skin treatment for seborrheic keratoses. It has advantages over conventional treatments that can lead to pain during treatment and scarring after healing.Keywords: seborrheic warts, solar lentigo, skin tumor, HIFU, dermoscopy, dermatology